Magnification in Periodontics: An Overview - Durgapal, Surabhi; Shetty, Mamatha (Journal of Health and Allied Sciences NU, 2022)
A plethora of changes in the concept and the techniques in dental sciences and an increase in patient awareness have spawned demand in advanced dental treatment encompassing elimination of disease with more precision and less discomfort. The use of magnification systems like microscopes is widespread in the medical field, and now it has successfully spread its wings in dentistry. Visual enhancement by using loupes or surgical microscopes can render refinement in the basic surgical procedures. Magnification periodontics refers to the wide range of procedures performed by the use of magnification systems like loupes and microscopes that allow convergence of ideas and efforts, which can make a huge impact on patients. Periodontal procedures are being increasingly performed nowadays that have enabled enhanced outcomes, which were difficult to achieve with the macrosurgery procedures when wound healing and tissue trauma are in consideration. The surgical operating microscope works within the microsurgical triad that includes illumination increased precision and magnification. The incorporation of smaller instruments and sutures and better visualization of the operating site enhance the surgical skills of the clinician. In the past decade, various periodontal procedures from the removal of calculus to the placement of dental implants have been performed using the surgical microscope, which have invariably provided favorable results. It is a topic of interest in the future of periodontal therapy.
Keywords: magnification; loupes; microscope; microsurgery